FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN STUNTING DI DESA PASIELUAH KABUPATEN NAGAN RAYA - Saragih, Frida Liharris; Octavia, Yunida Turisna (Jurnal Ilmiah Keperawatan, 2022)
Stunting is a problem of malnutrition caused by a lack of intake for a long time. The problem of stunting in Indonesia not only negatively affects physical health but also has a bad effect on optimal cognitive achievement. The causative factors include knowledge, income and culture of the local community. The purpose of this study is to determine whether there is a relationship between knowledge, income and culture of madeueng with the incidence of stunting in toddlers in Pasie Luah Village, Tadu Raya District, Nagan Raya Regency. This research method is quantitative with a cross sectional approach. The research was conducted in Pasie Luah Village, Tadu Raya District, Nagan Raya Regency. The study population was 53 people and the sample used a total sampling of 53 people. Data analysis was performed univariately and bivariately using the Chi Square test at a confidence level of 95% (0.05). The results showed that there was a relationship between the knowledge variable (p = 0.048) and the madeueng cultural variable (p = 0.030) with the incidence of stunting in toddlers, while in the income variable it was known that there was no relationship between parental income and stunting events in toddlers in Pasie Luah Village, Tadu Raya District, Nagan Raya Regency. It is hoped that the puskesmas can increase public knowledge by carrying out health promotion activities and efforts to reduce the number of applications of madeung culture. If public knowledge increases, it is hoped that madeueng culture can be avoided so that the prevention of stunting in toddlers can be prevented.